Quality of Work Life Among Faculty Members of Professional courses with Reference to Meerut District - Sukhija, Archana (Journal of Commerce and Trade, 2016)
Quality of work life (QWL) has not been a new phenomenon as it was started from 1972 when the term was used to discuss upon the "political movement" and "emerging new social science theories". First was the case with Western Europe and second was in U.S. This and other earlier movements in the area of QWL revealed the tendency of concept only with relation to labour participation and labour-management. With the advent of new technologies and rapid globalization, role of workers has changed dramatically as union-management relation got emphasis. Mere considering the people as machine or a component for the organization is the mania which will not be amused. As big as well as the biggest organizations have accepted the vitality of people in the organizations and these have even changed the concept of human resource so drastically in the way that new kind of cultures such as "GOOGLE-CULTURE", "YAHOO-CULTURE", "MICROSOFT CULTURE" etc. have been established on the planted earth and flourishing also. The present research has been focussed on QWL in respect of faculty members of professional courses.